Data communications and networking - Forouzan, Behrouz A.; Fegan, Sophia Chung (McGraw-Hill Higher Education, 2013)
The fifth edition of Behrouz Forouzan's Data Communications and Networking presents a comprehensive and accessible approach to data communications and networking that has made this book a favorite with students and professionals alike. More than 830 figures and 150 tables accompany the text and provide a visual and intuitive opportunity for understanding the material. This unique approach minimizes the need for heavy math content, allowing normally complicated topics to unfold graphically and visually rather than through the presentation of complex formulas. The new edition has been reorganized to showcase recent developments in the field and minimize or eliminate coverage of deprecated topics. In addition to the updated material included in each chapter, the text now features a chapter on the peer-to-peer paradigm, a full chapter on quality of service (QoS), additional coverage of forward error correction, coverage of WiMAX, and material on socket-interface programming in Java. The end-of-chapter material has also been significantly enhanced and now includes more than 630 questions, 600 problems, many lab assignments, programming assignments, and online applets that allow students to see problems and protocols in action. Technologies related to data communications and networking are among the fastest growing in our culture today, and there is no better guide to this rapidly expanding field than Behrouz Forouzan, an author whose visual, student-friendly approach has become a hallmark in a computer science instruction